2005
DOI: 10.1177/0265407505049325
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty management and adoptees’ ambiguous loss of their birth parents

Abstract: According to the National Adoption Information Clearing House (2000; http://www.calib.com/naic/statistics.htm) 120,000 children each year are adopted in or into the US. Much has been written about the attachment and adjustment issues adoptees experience, yet there has been no comprehensive study on the loss felt by adoptees as they reach adulthood. This study of 54 adult adoptees extends the literature on uncertainty management and ambiguous loss by examining how these forces inform one another in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 33 publications
4
78
1
1
Order By: Relevance
“…Although relational uncertainty has been primarily applied to romantic relationships (see, for example, Knobloch & Carpenter-Theune, 2004;Knobloch & Solomon, 1999;Knobloch, Solomon, & Cruz, 2001), recent research has found relational uncertainty to be a salient experience of stepchildren (Afifi & Schrodt, 2003;, siblings (Bevan, Stetzenbach, Batson, & Bullo, 2006;Floyd, 1997), and adult adoptees (Powell & Afifi, 2005). Viewed as a set, these findings demonstrate that relational uncertainty is a common experience within family relationships.…”
Section: Relational Uncertaintymentioning
confidence: 93%
See 1 more Smart Citation
“…Although relational uncertainty has been primarily applied to romantic relationships (see, for example, Knobloch & Carpenter-Theune, 2004;Knobloch & Solomon, 1999;Knobloch, Solomon, & Cruz, 2001), recent research has found relational uncertainty to be a salient experience of stepchildren (Afifi & Schrodt, 2003;, siblings (Bevan, Stetzenbach, Batson, & Bullo, 2006;Floyd, 1997), and adult adoptees (Powell & Afifi, 2005). Viewed as a set, these findings demonstrate that relational uncertainty is a common experience within family relationships.…”
Section: Relational Uncertaintymentioning
confidence: 93%
“…Furthermore, issues of relational uncertainty experienced within family relationships such as doubts experienced by adult adoptees (Powell & Afifi, 2005) and stepchildren are markedly different from the issues of relational uncertainty experienced in romantic relationships. In short, it appears that sources of relational uncertainty are evident in a variety of relationships, but the content of relational uncertainty varies by context.…”
Section: Relational Uncertaintymentioning
confidence: 95%
“…As transracial adoptees grow older, Correspondence concerning this article should be addressed to Richard M. Lee Lee & Quintana, 2005). At the same time, they may begin to experience feelings of loss of birth culture and family history and the growing awareness of racism and discrimination in their everyday lives (Meier, 1999;Powell & Affi, 2005). This feeling of loss, in turn, has been found to be associated with greater depressive symptoms and lower self-worth among domestically and internationally adopted preadolescents (Smith & Brodzinsky, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Only a small percentage of adoptees actively try to resolve this uncertainty by searching for their birth parents (Warner-Colaner & Kranstuber, 2010). Although the search for birth parents may be expected to lessen the degree of uncertainty experienced by adoptees, research by Powell and Afifi (2005) reported that levels of uncertainty and ambiguity actually increased with the active search for birth parents. Another challenge that adoptees' must face is the experience of living in their birth country.…”
Section: Adoption and Ambiguous Lossmentioning
confidence: 99%